Symmetric-component decoupled control of grid-connected inverters for voltage unbalance correction and harmonic compensation. (February 2020) - Zhang, Y.; Roes, M.G.L.; Hendrix, M.A.M.; Duarte, J.L.
Highlights: A control strategy is proposed to use of grid-interactive power converters for add-on local voltage support. The proposed control strategy requires only local measurements. Decoupled control of positive- and negative-sequence components is achieved by using resonant filters. A frequency-domain methodology is presented to analyse the sequence components and harmonics. Experiments validate the effectiveness of the strategy in voltage unbalance correction and harmonic reduction. Abstract: In this paper, a strategy is investigated for control of distributed generators to additionally support the local grid on top of conventional electricity generation. The strategy decouples unbalance and harmonic compensation in the phase sequences and the frequency domain for a grid-connected inverter with local unbalanced and distorting loads. Unlike conventional control schemes for grid-connected converters, the proposed strategy is designed to be sequence-asymmetric for the purpose of unbalanced and harmonic local voltage correction. A frequency-domain Norton equivalent model is derived to illustrate the working principle of the strategy. Accordingly, it is shown that following a frequency-domain decoupled method the fundamental positive-sequence, the harmonic symmetrical sequence, the fundamental zero-sequence and the fundamental negative-sequence components can be regulated independently. Consistent to the model analysis, experiments validate the reduction of the local voltage total harmonic distortion and unbalanced factor when the converter is programmed for both harmonic sinking and voltage unbalance correction.